Parametric sediment echo sounder survey during R/V Heincke cruise HE438 in the German Bight with link to raw data files - Svenja Papenmeier; H Christian Hass (PANGAEA, 2019)
Parametric sediment echo sounder data were collected during R/V Heincke cruise HE438 with a Innomar SES-2000 medium. Data recording was executed along 113 profiles in North Sea within German EEZ. The survey speed was 6-7 knots. The primary frequency is 100 kHz and the secondary 10-15 kHz.